Reflection of the strategic narrative of confrontation in non-governmental online media - Agnistikova, Olga I. (Известия Саратовского университета. Новая серия. Серия Филология: Журналистика, 2023)
The article deals with the problem of media displaying strategic narratives in the context of the domination of the antagonistic discourse in the relations between Russia and the West. The issue is becoming ever more urgent since the conflict component is being intensified on the global stage, which prompts the eagerness of a number of countries to impose their interpretation of what is happening as the only correct version, by means of promoting public agreement. On the example of several foreign online media the specific features of the narrative of confrontation are shown. Its structural elements are indicated, its particular properties are revealed. It is argued that the content of the constructed narrative is accusatory rhetoric, lying on the plane of foreign policy interstate relations. Several models of media representation of strategic narratives are characterized. The narrative of confrontation is revealed to have involved, besides the states and political leadership, people criticizing government, as the oppressed. It is emphasized that the main tool for constructing the narrative of confrontation is the use of discursive practices of constructing the “Other”, characterized by negative and evaluative semantics, which actualizes the image of the “alien” as an external enemy. Some topics are defined as the “framework” of the narrative in question; due to significant differences in the interpretation of events related to them, they sharpen the contradictions with the “Other” as with the discursive target. It was found that important conditions favorable to the functioning of the narrative of confrontation in the media are the elitist-official nature of the majority of news, as well as the declaration of the information war. It is concluded that the reliance on the same strategic narratives in journalistic materials acts as a factor of discursive limitation of the spectrum of evaluations of socially significant events, phenomena and processes, and the state of conflict of interpretations intensifies the antagonistic nature of the narratives broadcast in the media, activating the symbolic struggle between them for the exercise of discursive power.